A Semi-Field Approach to Testing Botanical Insecticides. Effects of Natural and Analogues Annonaceous Acetogenins on Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) - Ruiz Hidalgo, José (2021)
Annonaceous acetogenins enclose a large number of biological activities, among which the insecticidal stands out. Spodoptera frugiperda is a pest that affects corn crops among others and has a great capacity to develop resistance to traditional insecticides, which represents sufficient reasons for the search for new alternatives for their control. Methods. The objective of this study was to determine the appropriate concentration and screening new natural insecticides against second instar larvae of S. frugiperda, under glasshouse conditions on Zea mays L. Natural products such as annonaceous acetogenins and some acetylated and methoxy methylated ACG derivatives and the commercial product Lambda-cyhalotrin (LC) were evaluated.Results. The Percent mortalities of S. frugiperda larvae in glasshouse conditions were recorded after 24, 48 and 72 h of treatment application. The results showed that the acetogenins tested were significantly (P < 0.05) different in relation to pest mortality than untreated check. After 72 h of treatment application the highest percent mortalities were obtained with the mixture of two natural products, rolliniastatin-2 (5) (100 μg/mL) + squamocin (6) (100 μg/mL) + LC (50 μg/mL) that proved the most effective and gave (100%), while rolliniastatin-2 (5) at 100 μg/mL alone, gave lowest percent mortality (65%), followed by squamocin (6) at 100 μg/mL (55%) and LC at 50 μg/mL (30%). The acetylated and methoxy methylated ACGs derivatives caused very low mortality (25-35%).Conclusion. Natural acetogenins are promising metabolites for insect control. Derivatization of these compounds reduces their toxicity to early instar larvae.Optimal Formulation. It is recommended that mixture of rolliniastatin-2 (5) (100 μg/mL) + squamocin (6) (100 μg/mL) + LC (50 μg/mL) are used as a management option of S. frugiperda as components of integrated pest management. The results allow us to infer that the addition of natural GCAs synergizes the insecticidal activity of the commercial product. Finding a new ecological alternative for insect control.